Socio Demographic Determinants of Delivery Practice in Rural Women of Bangladesh (Delta Medical College Journal, 2013)
Background: Every year, world wide, 200 million women become pregnant. The development of urban areas allowed women to receive more care and treatment. However, in rural areas such measures are not available to every woman. Data on delivery practice of rural woman may help the social and public health planners and decision makers to minimize and prevent maternal mortality and morbidity ensuring safe motherhood.Objective: The aim of the study was to observe the delivery practice of rural women of Bangladesh. Materials and method: A cross-sectional study was conducted and data were collected from Dhamrai upazila, Dhaka, Bangladesh in April 2008. Total 159 women of reproductive age group at least having one child were selected purposively to elicit information on various demographic, socioeconomic, cultural and selected programmatic variables including maternal health care and delivery practices. Results: Among the respondents about 55% were literate. Majority (80%) of the respondents delivered at home and most of the them (71%) felt that home delivery was comfortable where as about 29% of the respondents were compelled to deliver at home due to family decision and financial constraint. Among the deliveries about 82% occurred normally and 18.2% were by cesarean section. A considerable percentage of deliveries (49%) were attended by traditional birth attendants. Blade was used for cutting umbilical cord in majority of the cases (74%) who delivered at home. Most of the respondents (90%) took ante natal check up and about 74% were vaccinated by tetanus toxoid. Conclusion: The results of the study suggest that a lot of work is still to do for the policy makers and health planners to target, plan, develop and deliver maternal health services to the rural women of Bangladesh. DOI: http://dx.doi.org/10.3329/dmcj.v1i2.15917 Delta Med Col J. Jul 2013;1(2):42-45